2001
DOI: 10.1074/jbc.m010217200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Water Molecules in the Association of Cytochrome P450cam with Putidaredoxin

Abstract: We have investigated the osmotic pressure dependence of the association between ferric cytochrome P450cam and putidaredoxin (Pdx) to gain an insight into the role of water molecules in the P450cam-reduced Pdx complexation amenable to physiological electron transfer. The association constant was evaluated from the electron transfer rates from reduced Pdx to P450cam. The natural logarithm of the association constant K a was linearly reduced by the osmotic pressure, and osmotic stress yields uptake of 25 waters u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
(30 reference statements)
4
20
3
Order By: Relevance
“…Importantly, in contrast to earlier studies (9,57-59), our results and data reported recently by others show that ET2 is considerably faster than ET1 at any Pdx: P450cam ratio (9,10,40,54,(60)(61)(62)(63) NIH-PA Author Manuscript NIH-PA Author Manuscript…”
Section: Effect Of Mutations On the Electron Transfer To Oxy-p450cam contrasting
confidence: 99%
See 1 more Smart Citation
“…Importantly, in contrast to earlier studies (9,57-59), our results and data reported recently by others show that ET2 is considerably faster than ET1 at any Pdx: P450cam ratio (9,10,40,54,(60)(61)(62)(63) NIH-PA Author Manuscript NIH-PA Author Manuscript…”
Section: Effect Of Mutations On the Electron Transfer To Oxy-p450cam contrasting
confidence: 99%
“…The second dramatic difference between the two reductive steps was that the D38A, W106A, and Δ106 mutations led to >99% drop in ET2 k cat . Taken together, the kinetic results indicate that (i) Asp38 and Trp106 are much more important in ET2 than in ET1 and (ii) that the P450cam-Pdx r complexes formed during the two reductive steps must be structurally different and/or use different ET paths.Importantly, in contrast to earlier studies (9,57-59), our results and data reported recently by others show that ET2 is considerably faster than ET1 at any Pdx: P450cam ratio (9,10,40,54,(60)(61)(62)(63) NIH-PA Author Manuscript NIH-PA Author Manuscript …”
contrasting
confidence: 99%
“…Several demonstrations of g L scale titers by engineered pathways show that, with careful optimization, cyanobacteria are promising hosts for heterologous NADPH-dependent metabolite production. These examples include the production of ethanol using alcohol dehydrogenase (Gao et al 2012), stereoselective reduction of various alkenes by an enoate reductase (Köninger (Kastritis et al 2011), 6 of which are electron transfer complexes, publically available from the Protein-Protein Interaction Affinity Database 2.0 website (http://bmm.crick.ac.uk/~bmmadmin/ Affinity/), and 10 additional electron transfer complexes (Holden et al 1994;Furukawa and Morishima 2001;Sétif 2006;Goñi et al 2009;Farooq and Roberts 2010). Gray crosses show non-redox complexes, and colored circles depict the 16 electron transfer complexes.…”
Section: Metabolic Engineering By Coupling Enzyme Activity To Photosymentioning
confidence: 99%
“…On the other hand, the addition of rat liver cytochrome b 5 (cyt b 5 ) and bacterial rubredoxins to oxy-P450cam can yield the hydroxylation product, whereas these non-physiological electron donors cannot transfer the first electron to ferric P450cam. Thus, the specific complex formation between P450cam and Pdx is required for the turnover reaction.We have studied the mechanism of the specific complex formation between P450cam and Pdx (19,20) and clarified that the P450cam⅐Pdx system exhibits unique features compared with other protein⅐protein ET complexes. Aoki et al (19) have reported the negative values for the changes in the enthalpy and entropy for the formation of the P450cam⅐Pdx complex determined from the isothermal titration and suggested that…”
mentioning
confidence: 99%
“…We have studied the mechanism of the specific complex formation between P450cam and Pdx (19,20) and clarified that the P450cam⅐Pdx system exhibits unique features compared with other protein⅐protein ET complexes. Aoki et al (19) have reported the negative values for the changes in the enthalpy and entropy for the formation of the P450cam⅐Pdx complex determined from the isothermal titration and suggested that…”
mentioning
confidence: 99%